META-ANALYSIS OF CONSTRUCTIVISM’S APPROACHES TO STUDENTS’ MATHEMATICAL ABILITY - Jumaida, Jumaida; Nuriadin, Ishaq; Jusra, Hella (FKIP Universitas Muhammadiyah Prof. DR. HAMKA, 2024)
This study examined the effectiveness of the constructivist approach in enhancing students' mathematical abilities through meta-analysis. Data were gathered from 20 journal publications implementing constructivist teaching strategies in mathematics instruction for Indonesian primary and high school students. Cohen's criteria were applied to assess effect sizes on students' mathematical abilities. The findings indicated that 15 studies (75%) demonstrated small effect sizes (0.0–0.20), suggesting a limited influence on students' mathematical skills. However, all studies showed higher average scores between pretests and posttests, highlighting the potential benefits of the approach. The remaining five studies (25%) reported moderate effect sizes (0.51–1.00), indicating a more substantial positive impact of constructivist methods on students' mathematical aptitude.